Residential revitalisation of inner city areas: a case study of Northbridge - Davidson, Dean A. (Curtin University, 1995)
The catalyst for this research has been the growing national interest in inner city living. Specifically this has come from local and state government, the housing and land development industry, and the general public over the last two decades. During this time there has generally been an increase in dwellings and residents within most Australian inner city areas. The last two decades has witnessed a continual barrage by public and private organisations as to the benefits of inner city living. However there has been negligible research from the inner city residents perspective. Most research to date has centered on inner city lifestyle benefits, what dwellings private developers are providing,and what local and state governments are doing to promote inner city living. This research has focused on Northbridge as a case study as an indicator of inner city Australian areas. The research identifies historical influences and changes in landuses in Northbridge since 1829 through to the 1990s with particular reference to the move from residential to commercial land uses, and the resurgence in residential land uses. This has included an analysis of the role and impact of local and state government, and commercial forces. A synoptic view reveals that landuse changes have been driven by the needs of commercial forces, with local and state government serving commercial before resident needs. A demographic profile of who the inner city residents are has been established. It has been revealed that the diversity of the inner areas is reflected in the demographics of the people that live there.Similarly the inner city household types and structures are varied, although most households are smaller than those of the middle or outer suburbs. Further research was undertaken to determine the relationship of the available dwellings in inner areas relative to what residents want in terms of dwelling design, size, location, open space, cost and affordability. The type of dwelling being built was found to be similar to what inner city residents want, although their cost creates inequitable access. The problems with inner city living and what support services are required for inner city residents was analysed. This was correlated with an analysis of transport needs, and the relationship between inner city residents, and the location of employment, retail and entertainment facilities. Most support services required by inner city residents were found to be available, although a need exists to improve specific services. Inner residents do rely on private vehicles, although to a lesser degree than middle or outer suburban dwellers and with less time spent travelling to access employment, retail and entertainment facilities. This research has essentially focused on the inner city residents needs, and the degree to which these needs have been fulfilled.The general consensus amongst local and state government, and private bodies involved in the supply of inner city dwellings is that building more dwellings will inject life into the inner areas. Unfortunately this is a simplistic view that is unlikely to create the bustling, lively streets envisaged. To revitalise the inner areas requires a closer examination of who the residents are that are moving into the inner areas' so as to enhance and not detract from the existing diversity. The concluding chapter of this thesis outlines recommendations that have been designed to promote equitable access to inner city dwellings and revitalisation of inner areas to ensure than not only is the inner city population increased, but that life is injected back into the inner city by the residents, and that there is more of a focus on resident, rather than commercial needs.